Modulation of Neuropathic Pain by Glial Regulation in the Insular Cortex of Rats - Choi, Songyeon; Kim, Kyeongmin; Kwon, Minjee; Bai, Sun Joon; Cha, Myeounghoon; Lee, Bae Hwan (Frontiers in Molecular Neuroscience, 2022)
The insular cortex (IC) is known to process pain information. However, analgesic effects of glial inhibition in the IC have not yet been explored. The aim of this study was to investigate pain alleviation effects after neuroglia inhibition in the IC during the early or late phase of pain development. The effects of glial inhibitors in early or late phase inhibition in neuropathic pain were characterized in astrocytes and microglia expressions in the IC of an animal model of neuropathic pain. Changes in withdrawal responses during different stages of inhibition were compared, and morphological changes in glial cells with purinergic receptor expressions were analyzed. Inhibition of glial cells had an analgesic effect that persisted even after drug withdrawal. Both GFAP and CD11b/c expressions were decreased after injection of glial inhibitors. Morphological alterations of astrocytes and microglia were observed with expression changes of purinergic receptors. These findings indicate that inhibition of neuroglia activity in the IC alleviates chronic pain, and that purinergic receptors in glial cells are closely related to chronic pain development.